Load Characteristics Analysis and Simulation Study of Electric Locomotive - Xiangzheng Xu; Qi Chen (Institute of Advanced Engineering and Science, 2014)
Electric locomotive is a kind of high power rectifier load, and its load characteristics will have a significant impact to safe, stable and economic operation of power system. This paper mainly analyses load characteristics of harmonic and reactive power for electric locomotive. Simulation model of electric locomotive is set up based on time trigger; it is so better conform to the dynamic characteristics of the electric locomotive. The mathematical model of SS8 electric locomotive is built, using MATLAB simulation software, dynamic simulation of electric locomotive is realized, and dynamic harmonic current and reactive power demand are obtained for traction supply network. The simulation results well reflect the operation situation of electric locomotive. It indicates that the research method of electric locomotive load characteristics is correct and effective. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4428